2019
DOI: 10.23910/ijbsm/2019.10.1.1940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Certain Insecticides against Diamondback Moth (DBM) Plutella xylostella on Cauliflower

Abstract: Studies were carried out in field condition during rabi, from November 2017 to February 2018 at Acharya N. G. Ranga Agricultural University, Agricultural College Farm, Naira, to evaluate the efficacy of certain newer insecticides against diamondback moth (DBM) Plutella xylostella on Cauliflower. The findings of the experiment revealed that all the chemicals evaluated against Diamond back moth larvae were significantly superior to check in protecting cauliflower from Diamond Back Moth at 3 and 7 days after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Similar findings were made" by Rahimgul and Sasya [4], and Stanikzi and Thakur [5]. Flubendiamide 20% WG (0.934) is found to be the next best treatment which is in line with the findings of Sharma et al, [6], Harika et al, [7] and Maity et al, [8] reported that Flubendiamide 20% WG (0.934) was found most effective in reducing the larval population of Diamondback moth as well as increasing the yield. Indoxacarb 14.5 SC (1.223) is found to be the next best treatment which is in line with the findings of Yadav et al, [9].…”
Section: Resultssupporting
confidence: 89%
“…Similar findings were made" by Rahimgul and Sasya [4], and Stanikzi and Thakur [5]. Flubendiamide 20% WG (0.934) is found to be the next best treatment which is in line with the findings of Sharma et al, [6], Harika et al, [7] and Maity et al, [8] reported that Flubendiamide 20% WG (0.934) was found most effective in reducing the larval population of Diamondback moth as well as increasing the yield. Indoxacarb 14.5 SC (1.223) is found to be the next best treatment which is in line with the findings of Yadav et al, [9].…”
Section: Resultssupporting
confidence: 89%
“…Highest yield and benefit cost ratio was recorded in Chlorantraniliprole 18.5% SC (325 q/ha) (1:6.37) is similar to the findings of Sharma et al, [8], Spinosad 45% SC (310 q/ha) (1:5.75) is similar to the findings of Gill et al, [9] and Gaddam et al, [10], Indoxacarb 14.5% SC (300 q/ha) (1:6.33) is similar to the findings of Harika et al, [11] and Gaddam et al, [10], Emamectin benzoate 5% SG (295 q/ha) (1:6.25) is similar to the findings of Akbar et al, [12], Bacillus thuringeinsis (1x10 8 CFU/ml) (280 q/ha ) (1:5.97) is similar to the findings of Choyon et al, [13] and Beauvaria bassiana (1x10 8 CFU/ml) (270q/ha) (1:5.72) is similar to the findings of Debbarma et al, [14] The treatments Metarhizium anisiopliae (1x10 8 CFU/ml) (260 q/ha) (1:5.50) is similar to the findings of Singh et al, [15], and the lowest yield was recorded in control (150 q/ha) (1:3.34) (Table 1).…”
Section: Resultssupporting
confidence: 89%
“…Nowadays, this insect pest resisted major insecticides viz, BHC and DDT (Dara 2020). Numerous recent pesticides were suggested to manage Plutella xylostella L. but the observation showed that 60% of the farmers cannot control this pest effectively (Harika et al, 2019). In the 1980s, there have several new pesticides were produced to reduce P. xylostella viz, triazophos, permethrin, fenvalerate, cartop, and methomyl.…”
Section: Introductionmentioning
confidence: 99%
“…As the elimination of chemical pesticides is unviable in the farmers, it has required the use of substitute eco-friendly insecticides for maintainable controlling of diamondback moth which can reduce it to minor pest status by the natural enemies and eco-friendly materials. The change of resistance against these outdated insecticides may be simply degraded by the new group of sustainable compounds to protect the environment (Harika et al, 2019). Keeping because of the seriousness of this pest and the economic importance of the cabbage crop, the current research was conducted to evaluate the effectiveness of the best-known insecticides viz., abamectin, spinosad, cypermethrin, and endosulfan under field conditions of a semi-arid zone at El-Kattawia, Abu-Hammad City, Sharkia Governorate, Egypt against Plutella xylostella on cabbage.…”
Section: Introductionmentioning
confidence: 99%